Association of Novel Mutations in the Vasoactive Intestinal Peptide Receptor-1 Gene with Egg Shell Thickness in Three Strains of Laying-Type Quail - Xinle Wang; Huricha Chen; Ying Lei; Qiankun Wang; Gan Li; Junyan Bai (Animals)
This study aimed to investigate the potential role of the vasoactive intestinal peptide receptor-1 (VIPR-1) gene polymorphisms and haplotypes in influencing egg production performance and egg quality parameters in laying-type quail. Genomic DNA was extracted from 150 quail across three strains: Chinese yellow (CY, n = 50), Beijing white (BW, n = 50), and Korean (KO, n = 50). We designed two pairs of primers and initiated PCR amplification, after which the amplified products were sent to a testing company for purification. Sanger sequencing was employed to identify single nucleotide polymorphisms (SNPs) within the VIPR-1 gene. Two SNP sites were selected for genotyping; g.1603402T>G was analyzed using PCR-RFLP with the BsrD I enzyme, while g.1614884A>G was genotyped using the HpyCH4 IV enzyme. The association results revealed that the g.1603402T>G site showed significant association with egg shell thickness (EST) in the BW strain (p < 0.05). There were no significant associations between these two loci and the remaining egg quality traits in the BW and KO strains (p > 0.05). Differences in egg quality and laying performance among haplotype combinations were not significant (p > 0.05). In conclusion, the VIPR-1 gene, with its identified polymorphisms and haplotypes, has potential as a molecular marker that could improve egg shell thickness in BW quail.